Risk of Thromboembolic Events in Atrial Fibrillation With Chronic Kidney Disease. Issue 1 (January 2015) - Zeng, Wu-Tao; Sun, Xiu-Ting; Tang, Kai; Mei, Wei-Yi; Liu, Li-Juan; Xu, Qing; Cheng, Yun-Jiu
Abstract : Background and Purpose—: Chronic kidney disease may increase the risk for ischemic stroke or systemic embolism in patients with nonvalular atrial fibrillation (AF). We conducted a meta-analysis to summarize all published studies to investigate the link between chronic kidney disease and risk of thromboembolic events in AF. Methods—: We performed a literature search using MEDLINE (source PubMed, 1966 to July, 2014) and EMBASE (1980 to July 2014) with no restrictions. Pooled effect estimates were obtained by using random-effects meta-analysis. Results—: Eighteen studies involving 538 479 patients and 41 719 incident thromboembolic events were identified. From the pooled analysis, AF patients with estimated glomerular filtration rate <60 mL/min compared with those with estimated glomerular filtration rate ≥60 mL/min experienced a significantly increased risk for developing thromboembolic events (relative risk, 1.62 [95% confidence interval, 1.40–1.87; P <0.001]). The annual rate of thromboembolic events increased by 0.41% (95% confidence interval, 0.17%–0.65%) for a 10 mL/min decrease in renal function. Addition of renal impairment to CHADS2 slightly improved the stroke risk stratification. Conclusions—: Impaired renal function is an independent predictor of stroke or systemic embolism in patients with nonvalvular AF. Consideration of renal function may improve stroke risk stratification in patients with AF. Abstract : Supplemental Digital Content is available in the text.